Examination of the sustainability of the sport facilities in the Northern Great Plain Region of Hungary - Kosztin, Nikolett; Balatoni, Ildikó (Applied Studies in Agribusiness and Commerce, 2015)
Developing sport into an industry has become a fundamental interest and a noticeable approach in Hungary in recent years. A socalled economic orientation can also be observed in the field of leisure time sports, which was made into law in Hungary in 2011 allowing the support of sport organisations and resulting in a number of infrastructural developments in Hungary. A wide range of development opportunities remain open in sports. This evaluation aims to introduce what significant sport-investment projects have been implemented in the Northern Great Plain region in recent decades and what effects these investments have had. Surveys have been used to reveal whether these facilities originating from years of sport developments are sustainable and to what extent these are exploited for organising sport events. Based on responses provided by a number of sport facilities – including ones built in the past and also ones opened recently – it can be concluded that sport in itself cannot solve the issue of operation and possible economic growth. Considering these aspects, it is important to incorporate, not only in operation but also during planning, the idea that current facilities must „serve” not solely sport events as these in themselves will not make them profitable but they must remain open for all sorts of social events as well.